Biocontrol Activity of Nonpathogenic Strains of Fusarium oxysporum: Colonization on the Root Surface to Overcome Nutritional Competition - Iida, Yuichiro; Ogata, Aya; Kanda, Hiroki; Nishi, Oumi; Sushida, Hirotoshi; Higashi, Yumiko; Tsuge, Takashi (Frontiers in Microbiology, 2022)
Fusarium oxysporum is a soil-borne fungal pathogen that causes vascular wilts in a wide variety of crops. Certain nonpathogenic strains of F. oxysporum are known to protect crops against F. oxysporum pathogens. We assessed the biocontrol activities of nonpathogenic mutants of F. oxysporum ff. spp. melonis and lycopersici generated by disruption of the FOW2 gene, which encodes a Zn(II)2Cys6-type transcriptional regulator essential for their pathgenicity. Pre-inoculation of melon or tomato roots with strain ΔFOW2 conidia markedly reduced disease incidence caused by the parental wild-type strain in a concentration-dependent manner of conidial suspensions of ΔFOW2 strains. The biocontrol effect caused by the ΔFOW2 pre-inoculation lasted for at least 7 days. Pre-inoculation of melon roots with the wild-type or ΔFOW2 strain of F. oxysporum f. sp. lycopersici and nonpathogenic F. oxysporum strain also led to biocontrol activity against F. oxysporum f. sp. melonis, indicating that the biocontrol activity of ΔFOW2 strains is due to its nonpathogenic nature, not to the FOW2 disfunction. Conidial germination and hyphal elongation of the wild-type strain were inhibited on melon root surface pre-inoculated with conidia of strains nonpathogenic to melon plants. Expression of defense-related genes was not significantly induced in roots and aboveground parts of melon seedlings preinoculated with ΔFOW2 conidia. Carbon source competition assay showed that nonpathogenic strains competed with the wild-type strain for a carbon source in soil. Strain ΔFOW2 also competed with the oomycete pathogen Pythium aphanidermatum for carbon and protected melon plants from P. aphanidermatum. Our results suggest that the biocontrol activity of the nonpathogenic F. oxysporum strains used in this study mainly depends on their extensive colonization of the root surface and outcompeting pathogens for nutrients.